CONSTRAINTS FACED BY SHGS AND JLGS IN DAIRYING IN BARPETA AND KAMRUP DISTRICTS OF ASSAM - J. K. SAIKIA3, NABANEETA PATHAK1 ; K. K. SAHARIA2 (Indian Journal of Animal Production and Management, 2017)
A study was conducted to identify the constraints faced by the members of SHGs and JLGs in dairying in Barpeta and Kamrup districts of Assam. A total of 100 respondents selected and information on their dairy characteristics and problems faced by them in dairy farming were elicited through a structured, reliable and valid interview schedule. The result shows about that high cost of feeds and fodder (83%), lack of quality breed (60%); inadequate veterinary facilities (56%), marketing (47%) etc were the major challenges of dairying to mitigate. Keywords: Dairy, Constraints, Joint Liability Groups (JLGs), Self Help Groups (SHGs)